Differences in cerebral oxygenation between healthy older and younger adults during the Multi‐Source Interference Task. (1st February 2022) - Kwan, Heather; Scarapicchia, Vanessa; Halliday, Drew; MacDonald, Stuart; Gawryluk, Jodie
Abstract: Background: Cognitive changes that accompany normal aging include declines in processing speed and executive function. Further research is needed to characterize the neurobiological underpinnings of these cognitive changes in older adulthood. The current study used functional near infrared spectroscopy (fNIRS), a neuroimaging technique that measures oxygenated hemoglobin (HbO), to examine differences in cerebral oxygenation between healthy younger adults (YA) and older adults (OA) during a measure of cognitive interference. Method: There were 34 participants sampled from two age group: YA (Mean age =28.1 years, SD=2.8, F=9) and OA (Mean age =70.9 years, SD=5.4, F=9). All participants were native English speakers, neurologically healthy, and had normal or corrected to normal vision. Participants completed the Multi‐Source Interference Task, a measure of cognitive interference with high and low‐demand conditions, while undergoing fNIRS recordings by a TechEn CW6 system with 34‐source‐detector channels over the PFC. The functional activation patterns, accuracy, and reaction time were compared between groups for each condition. Result: The functional results demonstrated a significant age‐related increase in HbO for OA in both conditions (p < 0.05). In the control condition, OA demonstrated increased HbO in 10 channels covering the left and mid‐anterior PFC in comparison to YA. In the interference condition, OA demonstrated increased HbO in 6 channels covering the mid‐anterior PFC in comparison to YA. During the control condition, OA and YA had the same accuracy (YA Mean= 0.99, OA Mean= 0.99, p>0.33), but OA were significantly slower (YA Mean= 545.63, OA Mean= 768.04, p<0.0001). During the interference condition, OA had lower accuracy (YA Mean=0.97, OA Mean=0.9, p< 0.0001) and were significantly slower (YA Mean=891.31, OA Mean=1114.5, p< 0.0001) than YA. Conclusion: The results from this study show that OA require greater activation in mid‐PFC regions, across both low and high‐demand conditions, relative to YA. These results are consistent with cognitive aging theories such as the compensation‐related utilization of neural circuits hypothesis (CRUNCH). Specifically, the findings suggest that OA recruit additional neural resources to achieve similar behavioural performance during low‐levels of cognitive interference, but that this same compensation may be insufficient to support behavioural performance at higher levels of interference.